Front Cover: Linkage Abundance and Molecular Weight Characteristics of Technical Lignins by Attenuated Total Reflection‐FTIR Spectroscopy Combined with Multivariate Analysis (ChemSusChem 6/2019) - Lancefield, Christopher S.; Constant, Sandra; de Peinder, Peter; Bruijnincx, Pieter C. A. (ChemSusChem, 2019)
The Front Cover shows that the traditional queuing up of samples for step‐by‐step structure analysis of technical lignins with HSQC NMR, 31P NMR and GPC, all requiring considerable amounts of time and/or access to high end equipment, can be avoided by taking an alternative, fast lane to gain the same quantitative structure information from a combination of readily accessible IR spectroscopy combined with chemometrics. Once the chemometrics model is in place, one single ATR‐FTIR measurement could then, in principle, replace the entire suite of traditional analysis methods. This would be particularly advantageous for routine structural characterization, such as those required during lignin fractionation processes, in quality control applications or when, for example, access to high end NMR equipment is limited. More information can be found in the Full Paper by Lancefield et al on page 1139 in Issue 6, 2019 (DOI: 10.1002/cssc.201802809).